Antiviral methods and protocols - Gong, Edwin Yunhao (Methods in molecular biology, 2013)
A Fluorescence-Based High Throughput Screening Assay to Identify HIV-1 Inhibitors -- A Homogeneous Time-Resolved Fluorescence Assay to Identify Inhibitors of HIV-1 Fusion -- Identification of HIV-1 Reverse Transcriptase Inhibitors Using a Scintillation Proximity Assay -- Biochemical Screening Assays to Identify HIV-1 Integrase Inhibitors -- HIV-1 Genotyping of the Protease-Reverse Transcriptase and Integrase Genes to Detect Mutations that Confer Anti-Retroviral Resistance -- In Vitro Kinetic Profiling of Hepatitis C Virus NS3 Protease Inhibitors by Progress Curve Analysis -- A Novel Hepatitis C Virus NS5B Polymerase Assay of De Novo Initiated RNA Synthesis Directed from a Heteropolymeric RNA Template -- Selecting and Characterizing Drug-Resistant Hepatitis C Virus Replicon -- A Cellular Replicon-Based Phenotyping Assay to Determine Susceptibility of Hepatitis C Virus Clinical Isolates to NS3/4A Protease Inhibitors -- Expression and Purification of Hepatitis C Virus Protease from Clinical Samples -- Surface Plasmon Resonance as a Tool to Select Potent Drug Candidates for Hepatitis C Virus NS5B Polymerase -- Amplification and Sequencing of the Hepatitis C Virus NS3/4A Protease and the NS5B Polymerase Regions for Genotypic Resistance Detection of Clinical Isolates of Subtypes 1a and 1b -- A Southern Blot Assay for Detection of Hepatitis B Virus Covalently Closed Circular DNA from Cell Cultures -- In Vitro Phenotyping of Recombinant Hepatitis B Virus Containing the Polymerase/Reverse Transcriptase Gene from Clinical Isolates -- Cell-Based Antiviral Assays for Screening and Profiling Inhibitors Against Dengue Virus -- A Duplex Real-Time RT-PCR Assay for Profiling Inhibitors of Four Dengue Serotypes -- High Throughput Screening Using Dengue Virus Reporter Genomes -- Fluorimetric and HPLC-Based Dengue Virus Protease Assays Using a FRET Substrate -- Expression and Purification of Dengue Virus NS5 Polymerase and Development of a High Throughput Enzymatic Assay for Screening Inhibitors of Dengue Polymerase -- Detection and Quantification of Flavivirus NS5 Methyl-transferase Activities -- Testing Antiviral Compounds in a Dengue Mouse Model -- Construction of Self-Replicating Subgenomic West Nile Virus Replicons for Screening Antiviral Compounds -- Methods for Screening and Profiling Inhibitors of Herpes Simplex Viruses -- In Vivo Evaluation of Antiviral Efficacy Against Genital Herpes Using Mouse and Guinea Pig Models -- A Fluorescence-Based High Throughput Screening Assay for Identifying Human Cytomegalovirus Inhibitors -- A Fluorescence-Based High Throughput Antiviral Compound Screening Assay Against Respiratory Syncytial Virus -- Screening and Evaluation of Anti-Respiratory Syncytial Virus Compounds in Cultured Cells -- Evaluation of Antiviral Efficacy Against Human Respiratory Syncytial Virus Using Cotton Rat and Mouse Models -- In Vivo Evaluation of Antiviral Compounds on Respiratory Syncytial Virus Using a Juvenile Vervet Monkey (Chlorocebus pygerythrus) Infection Model -- Methods to Determine Mechanism of Action of Anti-Influenza Inhibitors -- Methods for Evaluation of Antiviral Efficacy Against Influenza Virus Infections in Animal Models -- Development of a High Throughput Antiviral Assay for Screening Inhibitors of Chikungunya Virus and Generation of Drug-Resistant Mutations in Cultured Cells -- A Mouse Model of Chikungunya Virus with Utility in Antiviral Studies.
Keywords: Aufsatzsammlung; Molekularbiologie; Medizin; Viren